2019
DOI: 10.1002/alr.22343
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of two commercial house dust mite extracts for allergic rhinitis: a head‐to‐head study

Abstract: Background: Several studies have demonstrated the efficacy of house dust mite (HDM) immunotherapy in allergic rhinitis (AR). We aimed to compare the efficacy and safety of 2 commercial HDM extracts in a Chinese AR population. Methods:This was an open-label study. HDM-associated AR patients were randomized into Dermatophagoides pteronyssinus (Dp) extracts (Alutard SQ; ALK, Hørsholm, Denmark) and Dp/Dermatophagoides farinae (Df) extracts (NovoHelisen Depot [NHD]; Allergopharma, Reinbek, Germany) groups. All pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 24 publications
(38 reference statements)
1
6
0
Order By: Relevance
“…It is easy to understand that the majority of LRs happened in high dosage HDM extracts (No.4 vial) injection. The incidence of immediate LRs in preschool patients was similar to that observed in patients aged 5-60 years in our previous study [15]. This suggests that SCIT in age below 5 years old group is as tolerable as for children aged above 5 and adults.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…It is easy to understand that the majority of LRs happened in high dosage HDM extracts (No.4 vial) injection. The incidence of immediate LRs in preschool patients was similar to that observed in patients aged 5-60 years in our previous study [15]. This suggests that SCIT in age below 5 years old group is as tolerable as for children aged above 5 and adults.…”
Section: Discussionsupporting
confidence: 87%
“…In the confirmed AR children below 6 years old, the sensitization rate of HDM [including Dermatophagoides farina (Df) and Dermatophagoides pteronyssinus (Dp)] was 97.6% [13]. SCIT with commercial HDM extracts of Dp (Alutard SQ, ALK Hørsholm, Denmark) have been demonstrated to be effective in children with AR and/or asthma [14][15][16]. This study aimed to investigate the incidence of side effects and potential risk factors during HDM SCIT in preschool children with respiratory allergy.…”
Section: Introductionmentioning
confidence: 99%
“…Khinchi found that the SCIT group had a disease severity reduced to one‐third and the SLIT group to half the severity observed in placebo‐treated 20 . On the contrary, Li's study confirmed the equal efficacy and safety profile of both commercial extracts in HDM‐associated AR patients 21 . Our results suggested that SCIT treatment was more effective compared with SLIT treatment at different time points.…”
Section: Discussionmentioning
confidence: 52%
“…20 On the contrary, Li's study confirmed the equal efficacy and safety profile of both commercial extracts in HDM-associated AR patients. 21 Our results suggested that SCIT treatment was more effective compared with SLIT treatment at different time points. But the efficacy between the Alutard and NHD groups was comparable.…”
Section: Discussionmentioning
confidence: 59%
“…As a consequence, immunotherapy containing a mixture of DPT and DF is frequently prescribed, although a recent publication did not find differences in efficacy between two commercial mites´ extracts: one with DPT as single source and other with a mixture of DPT and DF (50/50) (24).…”
Section: Discussionmentioning
confidence: 99%